Diy Videolessons: miniseries to guide the design of video lessons for teaching English as an additional language - Reis, Susana Cristina dos; Schiefelbein, Layla (The ESPecialist, 2023)
The video lesson is a rising multimodal genre in literacy events in the digital context due to its intense use in online education. Therefore, studying the rhetorical organization of this genre, its consumption, production, and dissemination, is important to support new interdisciplinary studies. In this article, we present the rhetorical organization description of video lessons, through the analysis of 14 samples, and the proposal of digital material as a short series. Results indicate the relevance of the developed material, as it aimed to assist teachers in understanding the genre, typologies, and its production process for use in English as an additional language class